Three Essays in Investment Efficiency, Accounting Reporting Complexity, and Cybersecurity Breaches: Evidence from Corporate Tax Avoidance - Asiri, Mohammed (Curtin University, 2021)
This thesis comprises three essays that examine the association between corporate tax avoidance and investment efficiency, accounting reporting complexity (ARC) and cybersecurity breaches (CSBs). The results of this study indicate that there is a positive association between corporate tax avoidance and investment inefficiency. It is also found that the association is mediated by financial statement readability, financial statement comparability and product market competition. It is found that ARC is associated positively with firms’ reporting of UTBs. Additionally, the use of industry-specialist auditors magnifies the positive association between ARC and UTBs. It is found that there is a positive and significant association between the occurrence of cybersecurity breaches and corporate tax avoidance in both the full sample and the propensity score matched sample.